Nexus between logistics management practices and quality of health service delivery in ghana: a case study of Wa municipality - Patricia Atingawaya Tiyetibo; Foster Abrampa Opoku-Mensah; Isaac Quansah Amoafo (Discover Health Systems)
Abstract Efficient logistics management is essential for ensuring the timely availability of medical supplies, which directly affects patient care and overall service quality. Despite its critical role, there remains a significant gap in understanding how logistics management practices influence healthcare service delivery outcomes, particularly in underserved regions. The study answers the question: what are the impacts of logistics management practices on the quality of healthcare service delivery in the Wa Municipality of Ghana’s Upper West Region? Using a quantitative approach, the research evaluates the effects of logistical practices such as procurement, transportation, inventory, and management on service quality. The study revealed that although the correlation between logistics management practices and healthcare quality was low (r = 0.031), the significant relationship between logistics challenges and healthcare quality (R = 0.672) suggests that logistical difficulties substantially affect service outcomes. The model’s significant ANOVA results (F = 12.371, p = 0.000) demonstrate that logistics management practices account for a considerable variance in healthcare quality (R²=0.660), though other factors also contribute (Adjusted R²=0.425). These findings highlight the importance of addressing logistical inefficiencies as a strategic priority to improve healthcare service delivery in resource-constrained settings. By identifying key logistical challenges, this study provides evidence to inform policy and operational interventions aimed at enhancing the availability and quality of healthcare services, ultimately contributing to better patient outcomes and health system performance in the Wa Municipality and similar contexts.